THE EFFECT OF ANXIETY, CONFIDENCE, AND MOTIVATION ON THE PERFORMANCE OF NATIONAL VOLLEYBALL REFEREE PROVINCE OF NORTH SUMATRA - Arie Favian Syahmar Marpaung; Sudradjat Wiradihardja; Kurnia Tahki (Gladi : Jurnal Ilmu Keolahragaan, 2021)
This study aims to determine whether there is a significant effect between the exogenous variables of anxiety, confidence, and motivation with the endogenous variables of the performance of referees on duty in North Sumatra Province. The population in this study is the National Referee of North Sumatra Province. The sampling technique used was the purposive sampling method in which the national referees selected were adjusted to the criteria determined by the researchers as many as 50 national referees from various levels. The research method used is the descriptive quantitative method. The results of the data analysis carried out showed that 1) There was a significant influence between anxiety on the referee's performance of 0.854 or 73.7%, 2) There was a significant influence between self-confidence on the referee's performance of 0.842 or 70.9%, 3) There was a significant effect of a significant difference between motivation on the performance of the referee is 0.744 or 55.3%, 4) There is a significant effect between anxiety on the motivation of 0.841 or 70.8%, 5) There is a significant influence between self-confidence and motivation of 0.851 or 72.5 %, 6) There is a significant effect between anxiety through motivation on referee performance by 0.744 or 55.3%, 7) There is a significant effect between self-confidence through motivation on referee performance by 0.879 or 77.3%. The data collection technique in this study used a questionnaire instrument method in the form of statements on a Likert scale that had been validated by experts. So it can be concluded that several internal and external factors can affect the performance of the referee in leading the match such as anxiety, confidence, and motivation. Suggestions for the referee to be able to optimize the psychological condition before leading the game, to maximize the task of leading the match.